Radial scars diagnosed on breast core biopsy: Frequency of atypia and carcinoma on excision and implications for management. (December 2016) - Donaldson, Alana R.; Sieck, Leah; Booth, Christine N.; Calhoun, Benjamin C.
Abstract: Aims: The risk of finding carcinoma in excisions following a core needle biopsy diagnosis of radial scar is not well defined and clinical management is variable. The aim of this study is to determine the frequency of high-risk lesions, ductal carcinoma in situ, and invasive carcinoma in excisions following a core biopsy diagnosis of radial scar. Methods and results: Dedicated breast pathologists and radiologists correlated the histologic and radiologic findings and categorized radial scars as the target lesion or an incidental finding. High-risk lesions were defined as atypical hyperplasia or classical lobular carcinoma in situ. Of the 79 radial scars identified over a 14-year period, 22 were associated with atypia or carcinoma in the core biopsy. Thirty-seven (37) of the 57 benign radial scars underwent excision with benign findings in 30 (81%), high-risk lesions in six (16%), and flat epithelial atypia in one (3%). There were no upgrades to carcinoma. One patient with a benign radial scar developed a 3-mm focus of intermediate-grade estrogen receptor-positive ductal carcinoma in situ in the same quadrant of the ipsilateral breast 72 months after excision. One patient with an incidental un-excised benign radial scar was diagnosed with ductal carcinoma in situ at a separate site of suspicious calcifications. Conclusions: In this series, none of the benign radial scars was upgraded to carcinoma. Radial scar was the targeted lesion in all cases with high-risk lesions on excision. Surgical excision may not be mandatory for patients with benign incidental radial scars on core biopsy. Highlights: Pathologic and clinical follow-up is reported for a series of patients with radial scars diagnosed on breast core biopsy. Excision of benign radial scars resulted in no upgrades to carcinoma, targeted or incidental. Patients with benign radial scars diagnosed on breast core biopsy may be offered surveillance as an alternative to immediate surgical excision.